Z Genereations Perspective: Analysis of Islamic Learning through Tiktok Social Media - Aufia Aisa; Mega Kirana Dewi (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This final project entitled “Analysis of Generation Z Perspective at Pondok Putri Sabilul Huda Tambakberas Jombang in Learning Islam through Tiktok”. This research was conducted based on the behavior of Generation Z who is very dependent on cellphones and social media. Social media is closely related to generation Z. Moreover, Tiktok social media. In this highly developed era, educators are more creative in conveying their knowledge so that students (generation Z) do not experience boredom in learing Islam. In order to make students not feel overwhelmed by a lesson, learning is presented through the tiktok facility. In order to be better accepted by students. Most of the generation Z also entrust the answer to every problem and question from the internet. Without knowing it, not all life problems can be found on the internet.